Historic and constructional aspects of stone schools in Greece: the case of the Aristotle Municipality in Chalkidiki - Pachta, Vasiliki (Journal of Architecture and Urbanism, 2021)
Historic schools, built during the end of the 19th – beginning of the 20th century, were evolved according to the wider socio-economic changes that took place at regional, national and international level. Their construction usually followed specific principles, governed by their functional role and structural safety requirements. In this study, the historical background of school buildings in Greece is given, in an effort to assess their evolution and physiognomy. To this direction, 14 historic school buildings, located in the Aristotle Municipality of Chalkidiki, N. Greece, were studied, taking into account their architectural and constructional characteristics. These buildings were erected from 1871 up to 1958 and are nowadays mostly used as elementary schools. In some cases, they are in second use or abandoned. They concerned 1 up to 3 storeys buildings, with rectangular ground plan, symmetrically organized around a main corridor. Their size and dimensions varied according to their capacity. From the beginning of the 30’s, supplementary elements of reinforced concrete (slabs, beams) were added, in combination with the existing building techniques. Nowadays, they are generally preserved in good state, due to the consecutive interventions taken place during their service life. However, their documentation and identification as heritage structures should be further assessed, in order to convey the tangible and intangible values they incorporate in the next generations.